10‐Gbit/s Wireless Communication System at 300 GHz. Issue 3 (1st June 2013) - Chung, Tae Jin; Lee, Won‐Hui
Abstract : A 10‐Gbit/s wireless communication system operating at a carrier frequency of 300 GHz is presented. The modulation scheme is amplitude shift keying in incoherent mode with a high intermediate frequency (IF) of 30 GHz and a bandwidth of 20 GHz for transmitting a 10‐Gbit/s baseband (BB) data signal. A single sideband transmission is implemented using a waveguide‐tapered 270‐GHz highpass filter with a lower sideband rejection of around 60 dB. This paper presents an all‐electronic design of a terahertz communication system, including the major modules of the BB and IF band as well as the RF modules. The wireless link shows that, aided by a clock and data recovery circuit, it can receive 2 7 −1 pseudorandom binary sequence data without error at up to 10 Gbit/s for over 1.2 m using collimating lenses, where the transmitted power is 10 μW.